Crisis response in Latin America: Is the rainy day at hand? - Eduardo Fernández-Arias; Peter J. Montiel (Inter-American Development Bank, Research Department, 2009)
This paper examines the countercyclical policy options available to Latin American countries in the face of the current global economic crisis, concluding that most of the major countries in the region appear to possess the fiscal space (as measured by credible fiscal sustainability and debt headroom) to run prudent countercyclical fiscal deficits. Those countries should undertake a constrained fiscal expansion focused on productive public spending and financed by 'rainy day' funds - large stocks of foreign exchange reserves that they have accumulated during recent years - rather than by market borrowing. The recent surge in multilateral financial activity to alleviate market illiquidity, whether intended for reserve or budget support, strengthens the case for this policy prescription: with multilateral support, the appropriate policy response is more expansionary, and its financing is less reliant on market borrowing.
Keywords: E62; E63; F34; 330; countercyclical policy; fiscal space; international reserves; multilateral financial support; Finanzmarktkrise; Wirtschaftspolitik; Konjunkturpolitik; Lateinamerika